2019
DOI: 10.1016/j.heliyon.2019.e02359
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane-carbon microfiber composite coating for electrical heating of concrete pavement surfaces

Abstract: Electrically-heated pavements have attracted attention as alternatives to the traditional ice/snow removal practices. Electrically conductive polymer-carbon composite coatings provide promising properties for this application. Based on the concept of joule heating, the conductive composite can be utilized as a resistor that generates heat by electric current and increases the surface temperature to melt the ice and snow on the pavement surface. This research investigates the feasibility of applying an electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 110 publications
(178 reference statements)
1
5
0
Order By: Relevance
“…So, it is not possible to incorporate them into the cement mortar, which is why a separation and cutting process through a homogenization process is needed. In Figure 2e,f, the cut and separated microfibers can be observed where no change in the microfiber shape is watched, but they are no longer continuous microfibers, now they are shorter (approximate sizes of 15–30 µm), comparable to some studies reported in literature, where microfibers within micrometer scale length are used in cementitious materials [59]. These results confirm that the homogenization process is useful for the separation and cutting of electro-spun microfibers.…”
Section: Resultssupporting
confidence: 82%
“…So, it is not possible to incorporate them into the cement mortar, which is why a separation and cutting process through a homogenization process is needed. In Figure 2e,f, the cut and separated microfibers can be observed where no change in the microfiber shape is watched, but they are no longer continuous microfibers, now they are shorter (approximate sizes of 15–30 µm), comparable to some studies reported in literature, where microfibers within micrometer scale length are used in cementitious materials [59]. These results confirm that the homogenization process is useful for the separation and cutting of electro-spun microfibers.…”
Section: Resultssupporting
confidence: 82%
“…Similar conclusions were drawn in the research study performed by Sassani et al [ 107 ], who also identified that the addition of a calcium nitrite-based corrosion inhibitor admixture as a conductivity-enhancing agent (CEA) enhanced electrical conductivity and compressive strength and was particularly effective for samples with low fiber content. In another research conducted by Sassani et al [ 108 ], the authors investigated the feasibility of using polyurethane-carbon-microfiber (PU-CMF) composite coating for heating pavement in terms of durability, surface friction and volume conductivity. The authors found that the composite coating has great potential in the heat pavement system application; however, the only limitation was the construction cost, which can be reduced through detailed future studies.…”
Section: Applications Of Self-sensing Concretementioning
confidence: 99%
“…However, less research studies have been performed in this area. Two different approaches were used for the realization of heated pavement systems (HPS): electrically conductive coating (ECOT) and electrically conductive Portland cement concrete made of self-sensing material [ 9 , 107 , 108 ]. Lastly, the researchers monitored structural health with a variety of methods, including filler dispersion, composite rods and textile sensors [ 15 , 22 , 29 , 41 , 74 , 75 , 85 , 109 ].…”
Section: Applications Of Self-sensing Concretementioning
confidence: 99%
“…In composite and heterogeneous materials, such as asphalt and Portland cement concretes, electrical conductivity varies throughout the material's volume, and there are even nonconductive zones within the material. The electric current flows through heterogeneous, polymer-based, or cementitious electrically conductive composites in separate paths with varying current magnitudes creating different Joule heating zones [50][51][52]. Considering that part of the microwave-induced heat is conducted to the material's surface, and this amount of heat is proportional to the total amount of heat generated, it is possible to evaluate the heating efficiency from the surface temperature using an infrared imaging system.…”
Section: Deicing Performance In Terms Of Heat Distribution On the Specimens' Surfacesmentioning
confidence: 99%